Reexamining brand loyalty and brand awareness with social media marketing: A collectivist country perspective - Joseph Lok-Man Lee; Chammy Yan-Lam Lau; Charlaine Wai-Ga Wong (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: This study seeks to advance the literature by examining the mediating role of brand loyalty and the moderating impact of brand awareness in the relationships between social media marketing and collectivist Chinese behavior in the hospitality service context. This exploration is grounded in brand commitment and expectancy disconfirmation theories. Methods:Empirical testing was conducted on survey data gathered from 150 collectivist Chinese customers in Hong Kong, utilizing partial least squares structural equation modeling. Results:Brand loyalty plays a partial mediating role in the relationships between social media marketing and purchase intention as well as word-of-mouth. Additionally, brand awareness exerts a negative moderating influence on social media marketing-brand loyalty link. Implications:Recommendations are provided for front-line staff tasked with addressing communication challenges by effectively managing the hotel's social media account. They are strongly advised to steer clear of creating face-threatening situations and to demonstrate respect for the loyalty of Chinese collectivist customers. Furthermore, a negative brand awareness effect emerges when collectivist Chinese customers compare hotel brands with online travel agents.
Keywords: O35; M3; M31; 650; social media marketing; brand loyalty; brand awareness; purchase intention